PENGARUH HARGA DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PADA UMAYA HIJAB STORE DI KOTA BANDUNG - Sabila Azzahra Rahmani; Dadang Munandar (Jurnal Riset Multidisiplin Edukasi, 2025)
The Muslim fashion industry in Indonesia has grown rapidly, particularly in Bandung, which has become a hub for local hijab brands. However, Umaya Hijab Store faces challenges such as intense competition, fluctuating demand, and declining sales, making consumer retention a concern. This study aims to examine the influence of price and lifestyle on consumer purchasing decisions at Umaya Hijab Store Bandung. A quantitative method with descriptive and verification analysis was applied. The sample consisted of 88 respondents selected through purposive sampling, namely consumers who had purchased at the store. Data were analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination (R²) with SPSS software. The findings reveal that price has a positive and significant effect on purchasing decisions (p = 0.007 < 0.05), and lifestyle also has a positive and significant effect (p = 0.000 < 0.05). Simultaneously, both variables significantly influence purchasing decisions (p = 0.000) with an R² value of 60.7%. This study highlights the importance of competitive pricing strategies and understanding consumer lifestyles to strengthen purchasing decisions.